Singing Training Using the Zoltán Kodály Method for Preschool and Kindergarten Teachers in Jayapura District - Sahureka, Cosye Meilina; Fangohoy, Wouter; Mulder, Deysi O.; Parinussa, Nelinio; Polhaupessy, Yustinus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Singing training was conducted using the Zoltán Kodály approach for early childhood education and kindergarten teachers in Jayapura Regency to address the need to improve teachers' competence in effective music teaching for young children. Gaps in music education, caused by a lack of professional training, affect teachers' ability to integrate music in children's cognitive and social development. This service activity aims to empower teachers with the Kodály method, which uses simple and familiar songs to teach basic music concepts in a fun and interactive way. This service activity was carried out using the direct demonstration method by STAKPN Sentani Church Music Department lecturers, who practiced using the Kodály method with children's songs. The training results showed increased teachers' understanding of how music can be used as an effective educational tool, such as the Zoltán Kodály approach. In conclusion, the training made a real contribution to improving the quality of music teaching in PAUD and TK and supporting children's cognitive, social, and emotional development through a holistic and creative approach.